The Effect of Environmental Performance, Environmental Costs, and Environmental Disclosure on Profitability of Manufacturing Companies Listed in Indonesia Stock Exchange 2016 - 2020 - Fandy Wicaksono; Barkah Susanto; F Farida (Urecol Journal. Part B: Economics and Business, 2022)
This study aims to empirically examine the effect of environmental performance, environmental cost and environmental disclosure on profitability that is measured using the (ROA) as a market performance ratio. This type of research is quantitative research conducted using secondary data in the form of data from annual reports from 2016 to 2020. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2020. The sampling method uses purposive sampling and obtained a sample of 13 companies or 65 company samples. Hypothesis testing is done by using multiple linear regression analysis. The results of this study indicate that the environmental performance and environmental disclosure have a positive effect on profitability. However, environmental cost had no effect on the profitability.